Synthesis, Characterization and Electrical Properties of [PEO-LICLO4] SPE System: Optimizing LiClO4 Loading in PEO-Based SPE Films (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The most promising materials are SPEs in the field of material science and engineering. SPEs are the most effective materials for the compact nature of the solid state electrochemical system. Among the polymer hosts, polyethylene oxide (PEO) based composites were intensively studied. The aim of the present study is to optimize LiClO4 loading in to the PEO host with respect to film stability and conductivity. The structural and electrical properties of synthesized SPE films are also elaborated here. In this current work, Lithium ion conducting SPEs are prepared. PEO is used as a polymer host with lithium perchlorate (LiClO4) as added metal salt and various fillers distributed in the [85PEO+ 15LiClO4] SPE method.